Switching genes on and off in haemopoiesis. (22nd July 2008) - Garrick, David; De Gobbi, Marco; Lynch, Magnus; Higgs, Douglas R.
Abstract : At present, the molecular mechanisms by which stem cells commit to and differentiate towards specific lineages are poorly characterized, and will need to be better understood before stem cells can be exploited fully in experimental and clinical settings. Transcriptional regulation, the ability to turn genes on and off, lies at the heart of these processes of lineage commitment and specification. We have focused on fully understanding how these decisions are made at a single mammalian gene locus, the α-globin genes, which become up-regulated in a tissue- and developmental-stage specific manner during haemopoiesis. The studies summarized in the present article have revealed that complete regulation of this gene cluster involves not only activating mechanisms in expressing erythroid cells, but also repressing mechanisms, involving the Polycomb complex and histone deacetylases which are present in non-erythroid tissues. Taken together, these observations provide a well-characterized model of how gene expression is fully regulated during the transition from stem cells through lineage commitment and terminal differentiation.